PENGARUH PHYSICAL CAPITAL, HUMAN CAPITAL, DAN STRUCTURAL CAPITAL TERHADAP PROFITABILITAS, PRODUKTIVITAS DAN PENILAIAN PASAR PADA PERBANKAN INDONESIA: Studi kasus perbankan yang terdaftar di BEI Tahun 2008-2011 - Rahmadhani, Sari (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2013)
This study aimed to examine the effect of disclosure of intangible assetsin the banking company. Disclosure of intangible assets is an importantconcern for modern accounting disclosures aimed determine the ability of anintangible asset in improving profitability, productivity and marketvaluation. New types of intangibles such as employee competence,relationships with customers, simulation models, administration andcomputer systems are not recognized in the financial reporting model andconventional management. Testing of intangible assets is done by using thecomponents of capital, namely Physical Intellectual Capital, Human Capital,Structural Capital.This research was conducted by a quantitative method using secondarydata. The population of this study was obtained from the banks listed on theIndonesia Stock Exchange in the period 2008 - 2011. The study sample was12 Banks are selected using purposive sampling method. Analysis techniquesused is by using multiple linear regression model using SPSS. The resultsshowed results provide empirical evidence that the Physical capital does notaffect the profitability, productivity, and penilaiaan banking market inIndonesia. While human capital affect the profitability and marketpenilaiaan, but has no effect on the pebankan produkivitas. Structural capitaldoes not affect the profitability and market penilaiaan, but the effect on theproductivity of banking in Indonesia.